ANALISIS PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 -2020 - Ujung, Ekaedah; Masdiana P, Aria; Humaira, Rafiqah (Fakultas Ekonomi Universitas Al-Azhar Medan, 2024)
The focus of this research is to determine how the influence of operating cash flow and accounting profits of a company has an impact on stock returns on the Indonesia Stock Exchange BEI in 2018-2020 for investments in companies listed on the Indonesia Stock Exchange (BEI) in the manufacturing, food and beverage sectors. . A total of 27 businesses were selected as research subjects, and 10 businesses were selected as samples. SPSS 22 program, data were analyzed using the following methods: multiple linear regression, coefficient of determination test (R2), partial test (t), and simultaneous test.